Interest Rate Changes and Commercial Bank Revenues and Costs - Maisel, Sherman J.; Jacobson, Robert (Journal of Financial and Quantitative Analysis, 1978)
Sherman J. Maisel, Robert Jacobson, Interest Rate Changes and Commercial Bank Revenues and Costs, The Journal of Financial and Quantitative Analysis, Vol. 13, No. 4, Proceedings of Thirteenth Annual Conference of the Western Finance Association, June 20-26, 1978 (Nov., 1978), pp. 687-700